Management of Rheumatologic Immune-Related Adverse Events (Rh-irAEs) – An Overview of Immunosuppressive Therapies (Canadian Rheumatology Today, 2024)
Cancer treatment has entered a new era with the expanding role of immunotherapy, in particular immune checkpoint inhibitors (ICIs). ICIs, including those that target cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4), programmed death protein-1 (PD-1), and programmed death ligand-1 (PD-L1), work by blocking the intrinsic down-regulators of the immune system, leading to sustained activation of effector T-cells to enhance endogenous anti-tumour immune responses.